Problems and prospects for improving farm management in Costa Rica - Sánchez Gómez, José Pedro (London, Sydney : [editor no identificado], 1983)
Tesis (Master of Science in Agricultural Economics)--University of London, 1983.
Keywords: DESARROLLO AGRICOLA -- INVESTIGACIONES